Chiral phosphoric acid catalyzed enantioselective addition of thiols to in situ generated ketimines: Synthesis of N, S-ketals. Issue 2 (11th January 2017) - Unhale, Rajshekhar A.; Molleti, Nagaraju; Rana, Nirmal K.; Dhanasekaran, Sivasankaran; Bhandary, Subhrajyoti; Singh, Vinod K.
Graphical abstract: Highlights: Brønsted acid catalyzed enantioselective synthesis of N, S-ketals has been developed. The products are obtained in moderate to excellent yields and enantioselectivities. A known HIV-1 reverse transcriptase inhibitor has synthesized using this protocol. Abstract: The chiral Brønsted acid catalyzed enantioselective 1, 2-addition of thiols to in situ generated ketimines, derived from 3-hydroxyisoindolinones, has been studied. The protocol provides a variety of isoindolinone-derived N, S -ketals in up to 98% yield and up to 99% enantioselectivity. The products have been converted to a known non-nucleoside HIV-1 reverse transcriptase inhibitor and a 1, 3-thiazine derivative.